(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The use of robotic methods to restore walking after spinal cord injury is a promising area of modern rehabilitation that helps to improve patient independence. This review article discusses the effectiveness of robotic methods of rehabilitation for patients with incomplete spinal cord injuries, their impact on walking recovery, and comparative characteristics of different methods. The relevance of the article is due to the constant need to improve methods of functional recovery of patients with preserved motor activity. Robotic methods are an innovative approach that combines mechanical support with the potential of neuroplasticity. However, the question of the effectiveness of the intervention and the integration of these techniques into the practice of physical therapy remains open. The aim of this study is to summarise current scientific data on the use of robotic methods for walking recovery after incomplete spinal cord injury, with a focus on the following impact indicators: speed, endurance and ability to move independently. The study used a systematic review method that includes peer-reviewed scientific articles, observational studies, and clinical trials. The results of the analysis showed that the use of robotic methods improves functional performance: speed, endurance and independence, as evidenced by tests: 6MWT, 10MWT and WISCI II. The scientific novelty of the review is a comparative analysis of autonomous and combined robotic methods. The practical significance of the work lies in the possibility of using the obtained conclusions by physical therapists to optimise the strategy of walking rehabilitation, as well as to select the most appropriate robotic means for implementation in clinical practice.